Media Influence on the “Teen Mother and Student Pregnancy” Phenomenon - Buaclee, Chatree (University of the Thai Chamber of Commerce Journal Humanities and Social Sciences, 2014)
This article focuses on the criticism of some media outlets such as print media, films, online social networks and the Internet that intentionally stimulate sexual relationships among teenagers. Teenagers often use the Internet to communicate with people of the opposite sex, which sometimes leads to premature sexual relationships and thus results in “teen mother and student pregnancy” problems. Some pregnant teenagers opt to have an abortion, which is considered immoral and against Thai culture. Most young people do not have good enough media literacy skills in identifying whether their communicating friends are good or bad people who just want to have sex with them. Besides unintended pregnancy and abortion problems, those teenagers may be at risk of sexually transmitted diseases. These problems will surely have huge bed impacts on the future of these teenagers.